Peningkatan Kapasitas Tenaga Keuangan Organisasi Dakwah Muslimah Wahdah Daerah Bulukumba: Increasing the Capacity of Financial Staff of the Muslimah Dakwah Organization of Wahdah in the Bulukumba Region - Farida Aprianti (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Community Service (PkM) is one form of community service as one of the pillars of the Tridharma of Higher Education. The method of implementing the community service program begins with mapping problems and training material needs using SOAR analysis. After the analysis is carried out, appropriate training materials are prepared that are needed to increase the capacity of financial staff at MWD Bulukumba. The materials presented during the training include: Developing Basic Financial Management Skills; Building Professional Workforce Integrity; Normative Foundations of Non-Profit Organization Finance; Fundraising Management. This community service (PkM) aims to improve the knowledge, skills, and attitudes of the financial staff of Muslimah Wahdah Daerah (MWD) Bulukumba so that they are able to manage organizational finances effectively and with integrity. This activity is carried out in the form of classical training based on the Participatory Learning Method for two days, with a participatory approach, direct practice, and formative evaluation. The results of the activity showed a significant increase in participants' understanding of basic financial principles, budget preparation, personal integrity, and fundraising techniques. Evaluation is done through pretest-posttest, active observation, and practical assignments that show that participants not only understand the concept, but are also able to implement it directly. The contribution of this PkM is to form professional, integrity-based non-profit financial personnel who are ready to carry out the strategic mandate of the organization based on Islamic values.